UJI TOKSISITAS SUBKRONIS EKSTRAK ETANOL DAUN MENGKUDU (Morinda citrifolia L.) DENGAN PENETAPAN KADAR KREATININ DAN BUN TIKUS PUTIH - Rahmatudina, Farikha; Harjanti, Reslely; Widyasti, Jena Hayu (As-Syifaa Jurnal Farmasi, 2023)
The subchronic toxicity test of Noni (Morinda citrifolia L.) ethanol leaf extract have been studied. The purpose of this study was to determine the effect of subchronic toxicity of noni ethanol leaf extract (Morinda citrifolia L.) on increased levels of creatinine and BUN (Blood Urea Nitrogen) of white rats. Noni leaves were extracted by using the maceration method with 96% ethanol dissolution for 3 times 24 hours while occasionally stirring until a thick extract was obtained. Then the blood creatinine and BUN levels were determined before administering the test preparation and on day 28. The research was carried out for 28 days then continued for 14 days for the satellite group. The results of the subchronic toxicity testing that was carried out showed a double increase in creatinine and BUN levels compared to normal values. Noni leaf extract treatment caused an increase in creatinine and BUN levels in the subchronic toxicity test at doses of 250, 500 and 1000 mg/kg BW, and the highest increase in levels occurred in the 1000 mg/kg BW group